\(a^2+b^2+c^2+d^2+4\ge2\left(a+b+c+d\right)\)
\(\Leftrightarrow a^2+b^2+c^2+d^2+4\ge2a+2b+2c+2d\)
\(\Leftrightarrow a^2-2a+1+b^2-2b+1+c^2-2c+1+d^2-2d+1\ge0\)
\(\Leftrightarrow\left(a-1\right)^2+\left(b-1\right)^2+\left(c-1\right)^2+\left(d-1\right)^2\ge0\)\(\left(\text{luôn đúng với mọi a,b,c,d}\right)\)
\(\text{Vậy }a^2+b^2+c^2+d^2+4\ge2\left(a+b+c+d\right)\)
\(\text{Dấu "=" xảy ra khi a=b=c=d=1}\)
Cách khác cho bạn nè:
Áp dụng BĐT cô si cho 2 số không âm ta có:
\(a^2+1\ge2a\)
\(b^2+1\ge2b\)
\(c^2+1\ge2c\)
\(d^2+1\ge2d\)
Cộng vế với vế ta được a2+1+b2+1+c2+1+d2+1>2a+2b+2c+2d
=>a2+b2+c2+d2+4>2(a+b+c+d)